Evaluación de aprendizajes con herramientas innovadoras y colaborativas - Rodríguez Calvopiña, Cinthya Alexandra (2022)
Education is one of the factors exposed to constant changes where the integration of new technologies allows teachers and students to adapt to a new era. The some way, the of current education purpose is to achieve in the student the know-how practice, that is, take theoretical knowledge is put into practice in everyday life. In this sense, it is necessary to into account the earning assessment development with the technological tools support. The aim this research was to develop the learning assessment with innovative and collaborative tools for the teaching-learning process improvenment in the second-year students from "Victoria Vásconez Cuvi- Simón Bolívar- Elvira Ortega education units" from Latacunga canton, Cotopaxi province of at school year 2022. The research project is methodololly was based on qualitative research, because it allowed to understand the educational reality, further, it was used qualitative research stages: preparatory, analytical and informative fieldwork, proposal and document for the search in relation to the study object variables, field research was also used for data collection. The method was inductive, the technique was interview with its interview guide tool, which allowed getting fundamental information about innovative and collaborative tools use for the learning assessment. Finally, as a made research result, it was got the analysis writing, interpretation and got information problem. This research contributes to the innovative and collaborative tools integration as part learning assesment, in order to motivate, create and develop new educational practices in the student.